Structural diversity, magnetic properties and luminescence of NiII, CoII and ZnII coordination polymers derived from 3, 3′‐[(5‐carboxy‐1, 3‐phenylene)bis(oxy)]dibenzoic acid and 1, 10‐phenanthroline. Issue 12 (6th November 2019) - Yang, Dong-Dong; Lu, Li-Ping; Zhu, Miao-Li
Abstract : Three coordination polymers based on 3, 3′‐[(5‐carboxy‐1, 3‐phenylene)bis(oxy)]dibenzoic acid and 1, 10‐phenanthroline have been prepared and structurally characterized, and the magnetic properties of the Ni II /Co II complexes and the luminescence properties of the Zn II complex were investigated. Abstract : Three novel coordination polymers (CPs), namely poly[[di‐μ‐aqua‐bisμ4 ‐3, 3′‐[(5‐carboxylato‐1, 3‐phenylene)bis(oxy)]dibenzoato‐κ 5 O 1 : O 1′, O 3 : O 5 : O 5′ bis(1, 10‐phenanthroline‐κ 2 N, N ′)trinickel(II)] dimethylformamide 1.5‐solvate trihydrate], [Ni3 (C21 H11 O8 )2 (C12 H8 N2 )2 (H2 O)2 ]·1.5C3 H7 NO·3H2 O n, (I), poly[[di‐μ‐aqua‐bisμ4 ‐3, 3′‐[(5‐carboxylato‐1, 3‐phenylene)bis(oxy)]dibenzoato‐κ 5 O 1 : O 1′, O 3 : O 5 : O 5′ bis(1, 10‐phenanthroline‐κ 2 N, N ′)tricobalt(II)] diethylamine disolvate tetrahydrate], [Co3 (C21 H11 O8 )2 (C12 H8 N2 )2 (H2 O)2 ]·2C2 H7 N·4H2 O n, (II), and catena ‐poly[[aqua(1, 10‐phenanthroline‐κ 2 N, N ′)zinc(II)]‐μ‐5‐(3‐carboxyphenoxy)‐3, 3′‐oxydibenzoato‐κ 2 O 1 : O 3 ], [Zn(C21 H12 O8 )(C12 H8 N2 )(H2 O)] n, (III), have been synthesized by the reaction of different metal ions (Ni 2+, Co 2+ and Zn 2+ ), 3, 3′‐[(5‐carboxy‐1, 3‐phenylbis(oxy)]dibenzoic acid (H3 cpboda) and 1, 10‐phenanthroline (phen) under solvothermal conditions. All the CPs were characterized by elemental analysis, single‐crystal and powder X‐ray diffraction, FT–IR spectroscopy and thermogravimetric analysis. Complexes (I) and (II) have isomorphous structures, featuring similar linear trinuclear structural units, in which the central Ni II /Co II atom is located on an inversion centre with a slightly distorted octahedral [NiO6 ]/[CoO6 ] geometry. This comprises four carboxylate O‐atom donors from two cpboda 3− ligands and two O‐atom donors from bridging water molecules. The terminal Ni II /Co II groups are each connected to the central Ni II /Co II cation through two μ1, 3 ‐carboxylate groups from two cpboda 3− ligands and one water bridge, giving rise to linear trinuclear [ M 3 (μ2 ‐H2 O)2 ( R COO)4 ] ( M = Ni 2+ /Co 2+ ) secondary building units (SBUs) and the SBUs develop two‐dimensional‐networks parallel to the (100) plane via cpboda 3− ligands with new (3 2 ·4)2 (3 2 ·8 3 ·9)2 (3 4 ·4 2 .8 2 ·9 4 ·10 3 ) topological structures. Zinc complex (III) displays one‐dimensional coordination chains and the five‐coordinated Zn atom forms a distorted square‐pyramidal [ZnO3 N2 ] geometry, which is completed by two carboxylate O‐atom donors from two distinct Hcpboda 2− ligands, one O atom from H2 O and two N atoms from a chelating phen ligand. Magnetically, CP (I) shows weak ferromagnetic interactions involving the carboxylate groups, and bridging water molecules between the nickel(II) ions, and CP (II) shows antiferromagnetic interactions between the Co 2+ ions. The solid‐state luminescence properties of CP (III) were examined at ambient temperature and the luminescence sensing of Cr2 O7 2− /CrO4 2− anions in aqueous solution for (III) has also been investigated.